174k views
22 votes
A student is trying to solve the system of two equations given below:

Equation P: y + z = 6
Equation Q: 5y + 9z = 1

Which of the following is a possible step used in eliminating the y-term?

A: (y + z = 6) ⋅ 9
B: (y + z = 6) ⋅ −5
C: (5y + 9z = 1) ⋅ 9
D: (5y + 9z = 1) ⋅ 5

1 Answer

6 votes

Answer: B: (y + z = 6) × -5

Explanation:

if you multiply 'y' by -5 it turns into -5y. Therefore when you add -5y and 5y together, you get 0y which is what you want when eliminating the y-term.

User Maymay
by
6.5k points